Can alexithymia be assessed through an interview in adolescents? The Toronto Structured Interview for Alexithymia: Reliability, concurrent validity, discriminant validity, and relationships with emotional-behavioral symptoms - Muzi, Stefania; Di Trani, Michela; Renzi, Alessia; Pace, Cecilia Serena (Frontiers in Psychiatry, 2023)
Alexithymia is connected to adolescents’ psychopathology, but the current methods of assessment present limitations. The Toronto Structured Interview for Alexithymia (TSIA) was developed to overcome the limits of the main used self-rating scale in adults, but no studies investigated its feasibility with adolescents. This study involved 95 community adolescents aged 12-19 years. Adolescents were assessed with the TSIA, the 20-item Toronto Alexithymia Scale (TAS-20), the Verbal Comprehension Index of the WISC-IV for verbal skills, and the Child Behaviour Checklist and Youth Self Report for emotional-behavioural symptoms. The aims were to investigate the TSIA internal consistency, concurrent validity with the TAS-20, discriminant validity with participants’ verbal skills, and relationships with emotional-behavioral symptoms. TSIA showed good internal consistency, concurrent validity with the TAS-20 (except for factor DDF), and independence by participants’ verbal skills, but few relationships with emotional-behavioural symptoms. In conclusion, TSIA showed some good psychometric proprieties but little convergence with research findings obtained with the TAS-20, suggesting the need for further research to check the feasibility of using the TSIA with adolescents. Meanwhile, a precautionary multi-method assessment of alexithymia is recommended.